2016
DOI: 10.5194/acp-16-525-2016
|View full text |Cite
|
Sign up to set email alerts
|

Sources of nitrogen deposition in Federal Class I areas in the US

Abstract: Abstract. It is desired to control excessive reactive nitrogen (Nr) deposition due to its detrimental impact on ecosystems. Using a three-dimensional atmospheric chemical transport model, GEOS-Chem, Nr deposition in the contiguous US and eight selected Class I areas (Voyageurs (VY), Smoky Mountain (SM), Shenandoah (SD), Big Bend (BB), Rocky Mountain (RM), Grand Teton (GT), Joshua Tree (JT), and Sequoia (SQ)) is investigated. First, modeled Nr deposition is compared with National Trends Network (NTN) and Clean … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…The reported contributions from lightning are: 0-7% of total N deposited and 1-17 % of total oxidized nitrogen (NO y ) across eight biodiversity hotspots worldwide (although with only 2.3 Tg N yr −1 of lightning NO x ) [113], 0.5 and 4 % of total N deposited, respectively, over the Yellow and South China Seas [192], and 1-22 % of total N deposited at eight US National Parks [84].…”
Section: Nitrogen Depositionmentioning
confidence: 98%
“…The reported contributions from lightning are: 0-7% of total N deposited and 1-17 % of total oxidized nitrogen (NO y ) across eight biodiversity hotspots worldwide (although with only 2.3 Tg N yr −1 of lightning NO x ) [113], 0.5 and 4 % of total N deposited, respectively, over the Yellow and South China Seas [192], and 1-22 % of total N deposited at eight US National Parks [84].…”
Section: Nitrogen Depositionmentioning
confidence: 98%
“…Satellite observations of tropospheric NO 2 columns have been used extensively to infer NO x emissions and their trends (Leue et al, 2001;Martin et al, 2003;Richter et al, 2005;Boersma et al, 2008). OMI NO 2 observations from the early part of the record showed decreasing trends over the US consistent with the decreases in NO x emissions reported by the NEI (Russell et al, 2012;Duncan et al, 2013Duncan et al, , 2016Krotkov et al, 2016) and also consistent with trends in NO 2 concentrations observed from surface networks (Kharol et al, 2015;Lamsal et al, 2015;Lu et al, 2015;Tong et al, 2015;Zhang et al, 2018).…”
mentioning
confidence: 60%
“…For example, the National Critical Loads Database (NCLD) provides policy makers and land managers a clearinghouse of information for assessing current deposition vs. critical loads ("exceedance") and potential impacts of proposed pollution-producing activities (Blett et al 2014; database available online). 6 Such information is particularly applicable to Class I airsheds, which are federally designated areas including national parks (Organic Act of 1916, 16 USC 1-4) and wilderness areas (Wilderness Act of 1964, 16 USC 1131-1136 in which perturbation of ecosystems or degradation of long-distance visibility violates their founding legislation (Bowman et al 2012, Lee et al 2016, Williams et al 2017.…”
Section: Introductionmentioning
confidence: 99%